Connections between the Market Pricing of Accruals Quality and Accounting‐Based Anomalies* - Du, Kai; Jiang, Xin Daniel (Contemporary Accounting Research, 2020)
ABSTRACT We examine whether prior findings on the market pricing of accruals quality (AQ) can be attributed to other forms of accounting‐based anomalies. Using hedge portfolio analysis and cross‐sectional regressions, we find that the return predictive power of AQ overlaps with several other accounting signals. We also find that, similar to other accounting‐based anomalies, especially the accruals anomaly, the AQ pricing effect (i) is likely due to mispricing instead of risk pricing, (ii) is attenuated in recent years, and (iii) disappears among firms with cash flow forecasts or long‐term growth forecasts. Our findings highlight the importance of controlling for existing return predictive signals when evaluating the market pricing of AQ.